Analisis Faktor-Faktor Yang Mempengaruhi Pelaporan Keuangan Melalui Internet (Internet Financial Reporting) Dalam Website Perusahaan - Thamrin, Minarthi Mayasari; Djou, Laurentius D Gadi; Sayang, Sabulon (Program Studi Akuntansi Universitas Flores, 2021)
This study aims to analyze the factors that affect financial reporting via the internet, which consists of company size, liquidity, leverage, and listing age. The type of data used is secondary data. There are 30 companies included in the sample criteria. This study uses a causal design which is useful for analyzing the relationship between one variable and another. The research technique used was sampling based on criteria. The data analysis method used is a quantitative approach consisting of classic assumption tests, fit tests, and hypothesis testing. The results showed that company size, liquidity, leverage, and listing age had a simultaneous effect on financial reporting via the internet. Partially, only the liquidity structure variable has a significant effect on financial reporting via the internet (IFR).